CONSUMING GENDER AND DISABILITY IN INDONESIAN FILM - Novi Kurnia (Asosiasi Pendidikan Tinggi Ilmu Komunikasi (ASPIKOM), 2017)
This study aims to examine the film audience reception on gender and disabilities representation towards What We Don’t Talk About When We Talk About Love (Yang Tidak Dibicarakan Ketika Membicarakan Cinta, 2013). This film directed by a prominent Indonesian woman film director, Mouly Surya, and produced in 2013. Such audience study is very important in the scholarship of women and Indonesian films dominated by studies on women representation in the film and women filmmakers. Employing reception analysis based on Stuart Hall’s work, this study involves six Indonesian students as informant of a series of in-depth interviews. The study finds that the personal experiences and knowledge of informants, as well as their film habits, but not their gender, influences their interpretation toward the issue of gender and disabilities in the film.